2017
DOI: 10.1111/jfb.13284
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the biology of two rarely seen deep‐sea chimaerids, Chimaera carophila and Hydrolagus homonycteris

Abstract: Chimaera carophila (n = 45) and Hydrolagus homonycteris (n = 11), two deep-sea chimaerids rarely caught in the waters off New Zealand, were collected from research trawl catches and commercial fishery catches around New Zealand at depths between 400 and 1300 m, between 2014 and 2016. Additional preserved specimens of both species (n = 58) from museum collections were analysed for size, sex and maturity. External assessment of male claspers and a combination of internal assessments of female gonad mass and ovid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The consistency in toothplate and VO morphology observed across the genera Chimaera , Hydrolagus , and Harriotta is complemented by previous studies that have described comparable diet patterns across these groups (Dunn et al, ; Jones, ; Finucci et al, ). Diets of these species consist predominately of crustaceans, sea urchins, molluscs, and polychaetes, which would require grinder toothplates for mastication (Huber et al, ).…”
Section: Measurements Of Chimaeroid Specimens Including Chimaera Lensupporting
confidence: 64%
“…The consistency in toothplate and VO morphology observed across the genera Chimaera , Hydrolagus , and Harriotta is complemented by previous studies that have described comparable diet patterns across these groups (Dunn et al, ; Jones, ; Finucci et al, ). Diets of these species consist predominately of crustaceans, sea urchins, molluscs, and polychaetes, which would require grinder toothplates for mastication (Huber et al, ).…”
Section: Measurements Of Chimaeroid Specimens Including Chimaera Lensupporting
confidence: 64%
“…Life‐history studies on deepwater species in particular have been limited to a handful of species commonly caught as by‐catch in regional fisheries (e.g. Barnett et al., 2009; Finucci et al., 2017; Finucci et al., 2017). These studies have indicated ghost sharks are likely more productive than other chondrichthyans, for example Chimaera monstrosa has been shown to have a high intrinsic rebound potential relative to other deepwater chondrichthyans (Kyne & Simpfendorfer, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Holocephalian diversity is currently concentrated in oceanic environments below depths of 200 meters [17][18][19][20][21]. Given their ancient common ancestry with other vertebrates, deepwater chimaeras and ghost sharks lend credence to the hypothesis that mesopelagic and bathypelagic environments have served as a refuge for ancient biodiversity that has become rare or extinct in other ecosystems [22,23].…”
Section: Introductionmentioning
confidence: 99%